2012
DOI: 10.3899/jrheum.120600
|View full text |Cite
|
Sign up to set email alerts
|

Annual Medical Costs and Healthcare Resource Use in Patients with Systemic Sclerosis in an Insured Population

Abstract: In this 12 week dose-finding study of 194 patients, weekly subcutaneous dosing with pegsunercept showed beneficial effects in improving the signs and symptoms of RA. It appeared to be safe and well tolerated in this small number of patients. Significant clinical improvements were seen in patients in the 800 microg/kg group; however, this dose may be suboptimal, and further evaluation of this product with higher doses or a more frequent dosing regimen is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 29 publications
4
33
2
1
Order By: Relevance
“…Furst, et al also reported adjusted annual healthcare costs of $22,909 for patients with SSc and $6620 for matched controls, resulting in a cost difference of $16,288. The lower adjusted cost difference found in the current study ($12,820) may be explained by the different definition of matched controls used in Furst, et al 18 . The difference may also reflect that the Furst, et al study was conducted among patients in a managed care organization, where patients included in the current study were enrolled in fee-for-service health plans.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Furst, et al also reported adjusted annual healthcare costs of $22,909 for patients with SSc and $6620 for matched controls, resulting in a cost difference of $16,288. The lower adjusted cost difference found in the current study ($12,820) may be explained by the different definition of matched controls used in Furst, et al 18 . The difference may also reflect that the Furst, et al study was conducted among patients in a managed care organization, where patients included in the current study were enrolled in fee-for-service health plans.…”
Section: Discussioncontrasting
confidence: 69%
“…The finding that direct healthcare costs are significantly higher for patients with SSc than controls is consistent with the literature. A claims data study by Furst, et al 18 reported unadjusted annual healthcare (medical and pharmacy) costs of $21,625 for patients with SSc and $6859 for matched controls, resulting in a cost difference of $14,766. These costs are comparable to the unadjusted annual healthcare cost ($22,016) for patients with SSc and cost difference ($16,039) found in our current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimated yearly per‐patient direct, indirect and lost productivity costs range from 11,073 Euro in Italy (Belotti Masserini, Zeni, Cossutta, Soldi, & Fantini, ) to 18,453 Canadian dollars (126,006 Euro) in a Canadian sample (Bernatsky et al, ) to 17,365 US dollars (154,989 Euro) in a large US SSc population (Furst, Fernandes, Iorga, Greth, & Bancroft, ) to 22,459 Euro in a French cohort of SSc patients (Chevreul et al, ).…”
Section: Introductionmentioning
confidence: 99%